Tax Capacity and Tax Effort : Extended Cross-Country Analysis from 1994 to 2009 - Le, Tuan Minh (World Bank, Washington, DC, 2013)
One of the important factors for economic development is the existence of an effective tax system. This paper deals with the concept and empirical estimation of countries' taxable capacity and tax effort. It employs a cross-country study from a sample of 110 developing and developed countries during 1994-2009. Taxable capacity refers to the predicted tax-to-gross domestic product ratio that can be estimated empirically, taking into account a country's specific macroeconomic, demographic, and institutional features, which all change through time. Tax effort is defined as an index of the ratio between the share of the actual tax collection in gross domestic product and taxable capacity. The use of tax effort and actual tax collection benchmarks allows the ranking of countries into four different groups: low tax collection, low tax effort; high tax collection, high tax effort; low tax collection, high tax effort; and high tax collection, low tax effort. The analysis provides broad guidance for tax reforms in countries with various levels of taxable capacity and revenue intake.